Association between Folate Intake and the Risk of Lung Cancer: A Dose-Response Meta-Analysis of Prospective Studies - Zhang, Yu-Fei (Public Library of Science, 2014)
BACKGROUND: Studies have reported inconsistent results regarding the existence of an association between folate intake and the risk of lung cancer. The purpose of this study was to summarize the evidence from prospective cohort studies regarding this relationship by using a dose-response meta-analytic approach. METHODOLOGY AND PRINCIPAL FINDINGS: In September 2013, we performed electronic searches in PubMed, Embase, and the Cochrane Library to identify studies examining the effect of folate intake on the incidence of lung cancer. Only prospective cohort studies that reported the effect estimates about the incidence of lung cancer with 95% confidence intervals (CIs) for more than 2 categories of folate intake were included. Overall, we examined 9 cohort studies reporting the data of 566,921 individuals. High folate intake had little effect on the risk of lung cancer (risk ratio [RR], 0.92; 95% CI, 0.84–1.01; P = 0.076). Dose-response meta-analysis also suggested that a 100 µg/day increase in folate intake had no significant effect on the risk of lung cancer (RR, 0.99; 95% CI, 0.97–1.01; P = 0.318). Subgroup analysis suggested that the potential protective effect of low folate intake (100–299 µg/day) was more evident in women than men, while the opposite was true of high folate intake (>400 µg/day). Finally, subgroup analyses of a 100 µg/day increment in folate intake indicated that its potential protective effect was more evident in men than in women. CONCLUSION/SIGNIFICANCE: Our study revealed that folate intake had little or no effect on the risk of lung cancer. Subgroup analyses indicated that an increased folate intake was associated with a reduced risk of lung cancer in men. Furthermore, low folate intake may be a protective factor for women, and high folate intake for men.